Tag-Resource-User: A Review of Approaches in Studying Folksonomies - Lasić-Lazić, Jadranka; Špiranec, Sonja; Ivanjko, Tomislav (Qualitative and Quantitative Methods in Libraries, 2017)
This paper provides insight into main approaches to studying folksonomy based on its tripartite structure “tags-users-resources”. By conducting an exhaustive literature review in relevant scientific databases in LIS field, main approaches and methods in analyzing folksonomies will be covered. The field of research is approached through three main focuses: (1) tags - covering approaches in analyzing tag corpuses and structure; (2) users - carrying out studies for diverse communities of practice and (3) resources - covering research and methods dealing with the potential of folksonomy in providing new tools for information retrieval. The area of researching folksonomies is still fairly new, so theoretical perspective and research methods are still being defined. In that light, this paper provides a review of the field of research, and a corresponding framework for the study of the field of folksonomy and social tagging systems.